A disulfiram-loaded electrospun poly(vinylidene fluoride) nanofibrous scaffold for cancer treatment. (24th December 2019) - Xie, Chenchen; Ding, Ran; Wang, Xinyue; Hu, Cuihua; Yan, Jin; Zhang, Wenxiao; Wang, Ying; Qu, Yingmin; Zhang, Shuye; He, Peng; Wang, Zuobin
Abstract: Disulfiram (DSF), an FDA approved drug for the treatment of alcoholism, has shown its effectiveness against diverse cancer types. Thus, we developed a disulfiram-loaded scaffold using the electrospinning method to enhance the stability of DSF and to facilitate its appropriate distribution to tumor tissues. The drug release profile of the disulfiram-loaded scaffold was examined by high-performance liquid chromatography. We obtained mechanical and morphological characterizations of A549 cells treated with different scaffolds by various techniques to evaluate its antitumor properties. This work revealed that the cells after the treatment with the disulfiram-loaded scaffold exhibited a lower height and a larger elastic modulus compared with the untreated cells and those treated with the neat electrospun fibers. The changes were the indicators of cell apoptosis. Taken collectively, the results indicate that DSF was successfully incorporated into the electrospun fibers, and the disulfiram-loaded scaffold has great potential for inhibiting the regional recurrence of cancer.